If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8b + 3 = 5b + 7 Reorder the terms: 3 + 8b = 5b + 7 Reorder the terms: 3 + 8b = 7 + 5b Solving 3 + 8b = 7 + 5b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-5b' to each side of the equation. 3 + 8b + -5b = 7 + 5b + -5b Combine like terms: 8b + -5b = 3b 3 + 3b = 7 + 5b + -5b Combine like terms: 5b + -5b = 0 3 + 3b = 7 + 0 3 + 3b = 7 Add '-3' to each side of the equation. 3 + -3 + 3b = 7 + -3 Combine like terms: 3 + -3 = 0 0 + 3b = 7 + -3 3b = 7 + -3 Combine like terms: 7 + -3 = 4 3b = 4 Divide each side by '3'. b = 1.333333333 Simplifying b = 1.333333333
| 3(3x-7)=81(12x-3x) | | 2/12= | | e^7x=10 | | -7(3(-5)-4)+2= | | -4(3(-5)-5(2)-7)= | | 2-2x-6x=26 | | 5r^3+r^2=80r+16 | | 2h-1=1 | | 5(2(-5)+6)-12(-5)= | | -2(3-7a)=-38+6a | | F(x)=2x^2-5x-25 | | 2x-7(3x+5)=2x-49 | | 4x+10+x=-15 | | 6x^2-90x+336= | | 5x-11=-39 | | 12s+13=15 | | 8(2x+1)=9(1-x) | | -5+3-5(-5)+7+4(2)= | | 13+8= | | 12(-2(-5)+3)-3(-5)+9((-5)-9)= | | 8+5x=6+3x | | .50(8x+26)=13+4x | | -3/4v_4=1/3v-1/3 | | 9y^3=-21y^2-10y | | 18+m=42 | | -4x-2.3=5x-5.6 | | Log(x-4)=2 | | 2b^2+64=0 | | 11-3y=32 | | (3x+2y+y^2)dx+(x+4xy+2x^2)dy=0 | | 3(x+2)-9=28 | | -1+4x=-33 |